العلاقة بين أبعاد إدارة علاقات العملاء والأداء المصرفي دراسة ميدانية على المصارف الخاصة في محافظة اللاذقية - قاسم, سامر; كنعان, علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يوفر نظام إدارة علاقات العملاء ميزة تنافسية قوية للمنظمة تمكنها من البقاء في السوق. فهو يساعد الإدارة على متابعة تعاملات العملاء مع المنظمة، ويسمح للموظفين بالوصول لجميع المعلومات السابقة المتعلقة بالعملاء؛ وتكتسب إدارة علاقات العملاء أهميتها من خلال دورها في تكوين رؤية استراتيجية لتحقيق أهداف المنظمة في الحفاظ على العملاء ووصولهم إلى درجة الولاء من خلال التكامل مع سياسات التسويق وتطوير المنتجات لزيادة مبيعات المنظمة وتقديم العروض التي تجذب العميل المستهدف والتفاعل معه بما يضمن لها الحفاظ عليه. يهدف البحث إلى دراسة واقع تطبيق إدارة علاقات العملاء خلال فترة الأزمة (2011-2018) في المصارف الخاصة السورية في محافظة اللاذقية، ودراسة أبعاد إدارة علاقات العملاء في هذه المصارف، ثم دراسة تأثير هذه الأبعاد على مؤشرات الأداء التي تم قياسها من خلال مؤشرات: الربحية، وشكاوى العملاء، والعلاقات الوطيدة مع العملاء، رضا العملاء وولائهم. ولتحقيق ذلك تمّ صياغة فرضيتين رئيستين، واستخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample t. test، واختبار الارتباط الثّنائي Pearson Correlation. وقد توصل الباحث إلى عدّة نتائج أهمّها: التقييم الجيد لتوافر أبعاد إدارة علاقات العملاء في المصارف المدروسة، كما توجد علاقة طردية موجبة بين هذه الأبعاد والأداء. Customer Retention Management (CRM) provides a strong competitive advantage for the organization to stay in the market. It helps management to track customer interactions with the organization and allows employees access to all customer,s previous information; CRM gains its importance by creating a strategic vision to achieve the organization's goals of maintaining customers and reaching loyalty through integration with marketing policies and product development To increase the sales of the organization and to make offers that attract the target customer and interact with him in a way that ensures its preservation. The aim of the study is to define the reality of the application of CRM during the crisis period (2011-2018) in the Syrian private banks in Lattakia, and study the dimensions of customer relationship management in these banks, and then study the impact of these dimensions on the performance indicators that were measured through indicators of profitability, customer complaints, strong relationships with customers, customer satisfaction and loyalty. In order to achieve this, two main hypotheses were formulated. The researcher used the questionnaire technique to collect the data analyzed using statistical tests, the most important of which were the one-sample t. test, and the Pearson Correlation test. The researcher has reached several results, the most important of which is: a good evaluation of the availability of CRM dimensions in the studied banks, and there is a positive relationship between these dimensions and performance.